TRADUÇÃO E PARATRADUÇÃO DO ROMANCE CLOUD ATLAS (2004) DE DAVID MITCHELL NO BRASIL. - Amorim Caribé, Yuri Jivago (Trabalhos em Lingüística Aplicada)
This research brings some reflections on paratexts related to the English novel Cloud Atlas (2004), by David Mitchell and the process of translating this work, published in Brazil as Atlas de Nuvens (2016). The launch of the translation of this novel was widely publicized by important communication channels, with the special support from specialized literary critics. However, the translated novel is still not very known and read in Brazil, neither it is analyzed in the academic field. Thus, we worked especially with the concept of translation by Frías (2014 and 2015) to see what role the paratexts played in the final edition of that translated work. The conclusions lead us to a rethinking of the translation process, directly influenced by the concept of translation. They also lead us to reflect on the participation of paratexts as an important element of analysis in the process of literary translation.